Corporate Governance and Pension Fund Performance - Oskar Kowalewski (Contemporary Economics, 2012)
This study provides new evidence on the impact of governance on the performance of privately defined contribution pension plans. Using a hand collected data set on governance factors, the study shows that the external and internal governance mechanisms in pension plans are weak. One explanation for this weakness is the potential conflict between the pension beneficiaries and the fund's owner, which depends on who bears the investment risk in the pension plan. Hence, different governance factors are found to be important for pension fund return on invested assets and also for its economic performance. Consequently, the overall policy conclusion is that more focus should be put on the governance of the pension funds, taking into account the different interests of the beneficiaries and owners as it may determine their performance.
Keywords: G23; G28; G30; 330; pension funds; corporate governance; agency theory; performance